Homogenization of elastic properties of short-fiber reinforced composites based on measured microstructure data. (February 2016) - Müller, Viktor; Brylka, Barthel; Dillenberger, Felix; Glöckner, Robert; Kolling, Stefan; Böhlke, Thomas
Mechanical properties of short-fiber reinforced composites are crucially influenced by their microstructure. The microstructure itself is mainly governed by the manufacturing process like injection or compression molding. The main contribution of this paper lies in the homogenization of linear elastic properties using experimental microstructural information. For this purpose, the microstructure of injection-molded specimens made of polypropylene reinforced with 30wt.% of short glass fibers are analyzed through micro-computer tomography ( μ CT) measurements. Applying a recently developed segmentation algorithm, the spatial position, the orientation distribution and the length of the fibers are determined. This data is evaluated in terms of orientation tensors and length distribution, and is used within three mean field approaches: a self-consistent homogenization method, the interaction direct derivative estimate, which is based on the three-phase model, and a two-step bounding method. All methods account for the orientation, the length and the diameter distribution. The numerical results are compared to experimental tensile tests.